Numerical simulation on the pressure, turbulence, and λ2 vortex characteristics within the annular symmetric jet process under different vacuum degrees - Chai, Xinjie; Hu, Yuxi; Gao, Lishan; Qiu, Facheng; Cheng, Zhiliang (Asia-Pacific journal of chemical engineering, 2024)
The jet impingement flash technology represents a paramount research subject in the domain of heat and mass transfer. To augment its commercial potential, the conjunction of annular multi‐aperture jet impingement with negative pressure flash evaporation is introduced in this study. The employment of an annular nozzle array is integral to the enhancement of the heat and mass transfer efficiency between the phases. The Realizable k‐ε model is used in this study. The negative pressure flash vaporization model was also developed by introducing a mass source term and an energy source term based on the Mixture model. The flow characteristics are characterized using numerical simulation. Additionally, the λ2 vortex identification criterion is investigated the vortex structure. The simulation results exhibit good agreement with experimental findings, demonstrating that a higher initial vacuum leads to a stronger flashing effect and a more chaotic movement of the flow group within the flow field. Thus, this study provides a reference method for the structural design and optimization of annular symmetric jet impingement negative pressure deammonia chemical equipment for engineering applications.